Upaya Pemerintah Nagari dalam Mengatasi Fenomena Illegal Logging (Studi di Nagari Lubuk Karak Kecamatan IX Koto Kabupaten Dharmasraya) - Aprise, Igo; Muchtar, Henni; Hasrul, Hasrul; Bakhtiar, Yusnanik (Lembaga Yasin AlSys, 2025)
This research is motivated by the phenomenon of illegal logging in Nagari Lubuk Karak, Dharmasraya Regency. The problem of illegal logging is very troubling because it can lead to various natural disasters such as floods and landslides, this happens because of excessive logging and not having a permit. The phenomenon faced today is not only the responsibility of the central government and the police, but it requires the role of the village apparatus to invite and direct the community to prevent and overcome the phenomenon of illegal logging and preserve the forest. This study aims to determine the causes and describe the government's efforts in overcoming the phenomenon of illegal logging in Nagari Lubuk Karak, Dharmasraya Regency. This research is a qualitative-descriptive study with data collection techniques through observation, interviews, and documentation studies. The informant selection technique uses purposive sampling consisting of the Nagari Wali, Nagari Secretary, Community Leaders, and the Dharmasraya Regency Forestry Service. Data analysis techniques, namely: data reduction, data presentation, and conclusion drawing and verification. The data validity test uses source triangulation and technique triangulation. The results showed that some of the causes of illegal logging in Nagari Lubuk Karak were: The desire of the community to get instant results in work, Low public awareness in preserving forests, Illegal Logging has a high economic value for the community, and Lack of supervision from the authorities. Meanwhile, the efforts made by the Lubuk Karak Nagari government in overcoming the phenomenon of illegal logging, namely: Making local regulations, Supervision, Cooperating with related agencies, Firm and critical in granting and revoking forest management licenses.